Doxorubicin carriers based on Au nanoparticles – effect of shape and gold-drug linker on the carrier toxicity and therapeutic performance. Issue 38 (29th March 2016) - Swiech, Olga A.; Opuchlik, Lidia J.; Wojciuk, Grzegorz; Stepkowski, Tomasz M.; Kruszewski, Marcin; Bilewicz, Renata
Abstract : Gold nanoparticles (AuNPs) prepared by the Turkevich method and near-IR absorbing non-spherical anisotropic nanotriangles (AuNTs) prepared by the thiosulfate method were used for doxorubicin binding. Abstract : Gold nanoparticles (AuNPs) prepared by the Turkevich method and near-IR absorbing non-spherical anisotropic nanotriangles (AuNTs) prepared by the thiosulfate method were used for doxorubicin binding. The drug was connected to the polyethyleneglycol modified gold nanoparticle by covalent peptide or pH-active hydrazone linkers. Their optical properties were studied by UV-vis spectroscopy. The shape and size of the nanoparticles were evaluated by SEM and DLS. Fluorescence studies demonstrated different drug release profiles depending on the pH. An MTT assay performed on two cell lines (A549 and HeLa) revealed that gold nanostructures modified with doxorubicin were more toxic than free doxorubicin. Viability tests and confocal microscopy revealed that the bond between the Au carrier and the drug determined the pathway of cell death – apoptotic in the case of peptide bonding and sudden and necrotic when a hydrazone linker was employed.